1987
DOI: 10.1111/j.1600-0536.1987.tb02634.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and irritant contact dermatitis from falcarinol and didehydrofalcarinol in common ivy (Hedera helix L.)

Abstract: Experimental and chemical investigations revealed that common ivy (Hedera helix susp. helix) contains 3 compounds which are powerful irritants and moderate sensitizers. Only 2 of these constituents, falcarinol and didehydrofalcarinol, are present in the plant during the whole year. Besides Panax ginseng and Schefflera arboricola, this is the third species of the Araliaceae in which these polyacetylenic sensitizers have been found. Falcarinol and didehydrofalcarinol also occur in Hedera helix subsp. canariensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 17 publications
0
48
0
7
Order By: Relevance
“…The relation between the clinical effect and the content of polyacetylenes has been investigated in Schefflera arboricola (Hayata) Merrill (Araliaceae) (dwarf umbrella tree), and the results showed that falcarinol (1) is a potent contact allergen, whereas related polyacetylenes such as falcarindiol (2) and falcarinone (4) had no effect on the skin . Falcarinol has been shown to be responsible for most of the allergic skin reactions caused by plants of the Apiaceae and Araliaceae (Hausen et al 1987;Hausen 1988;Murdoch and Demster 2000;Machado et al 2002). The allergenic properties of falcarinol indicate that it is very reactive towards mercapto and amino groups in proteins, forming a hapten-protein complex (antigen) (Figure 5.12).…”
Section: Allergenicitymentioning
confidence: 99%
“…The relation between the clinical effect and the content of polyacetylenes has been investigated in Schefflera arboricola (Hayata) Merrill (Araliaceae) (dwarf umbrella tree), and the results showed that falcarinol (1) is a potent contact allergen, whereas related polyacetylenes such as falcarindiol (2) and falcarinone (4) had no effect on the skin . Falcarinol has been shown to be responsible for most of the allergic skin reactions caused by plants of the Apiaceae and Araliaceae (Hausen et al 1987;Hausen 1988;Murdoch and Demster 2000;Machado et al 2002). The allergenic properties of falcarinol indicate that it is very reactive towards mercapto and amino groups in proteins, forming a hapten-protein complex (antigen) (Figure 5.12).…”
Section: Allergenicitymentioning
confidence: 99%
“…Allergic and irritant contact dermatitis caused by contact with ivy plants may occur. Polyacetylenes (falcarinol and didehydrofalcarinol) were identified as allergenic substances [12]. However, there are some theoretical concerns with regard to ivy leaves because of their saponin content.…”
Section: Discussionmentioning
confidence: 99%
“…It contains three powerful irritants and weak sensitizers, namely didehydrofalcarinol and falcarinol (Fig. 31) that have mod- erate sensitizing potentials [310,362,363]. These allergens or related molecules are also present in other members of this family, such as ginseng (Panax ginseng C. Meyer), Schefflera arboricola Hayata [310] or kakuremino (Dendropanax trifidus Makino) [364].…”
Section: Miscellaneous Plantsmentioning
confidence: 97%
“…Falcarinol, also contained in members of Araliaceae (see later section), is probably the delayed-type allergen present [309,310].…”
Section: Ranunculaceae (Buttercup Family)mentioning
confidence: 99%
See 1 more Smart Citation